PENENTUAN TARIF RAWAT INAP MENGGUNAKAN ACTIVITY BASED COSTING SYSTEM (STUDI KASUS RUMAH SAKIT DI SIDOARJO) - Sutopo Sutopo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
Determination of tariffs using an activity based costing system is a very important decision in the home. The purpose of this study is to determine the rate of inpatient services based on an activity based costing system that can be applied in hospitals so that accurate cost information can be achieved. Data collection techniques include observation, interviews, documentation. The results of this study indicate that the determination of rates with an activity based costing system is determined by several stages based on the activities used by each inpatient service so that it is an effective and efficient calculation method in determining the total cost of the product. The conclusion is that the determination of tariffs with an activity based costing system is an effective and efficient calculation method in determining the total cost of the product.